Restoration of Type 17 immune signaling is not sufficient for protection during influenza-associated pulmonary aspergillosis - Ahmad, Aijaz; Singh, Ravineel B.; Nickolich, Kara L.; Pilewski, Matthew J.; Ngeow, Caden; Frempong-Manso, Kwame; Robinson, Keven M. (Frontiers in Immunology, 2025)
IntroductionInfluenza-associated pulmonary aspergillosis (IAPA) is a severe complication of influenza infection that occurs in critically ill patients and results in higher mortality compared to influenza infection alone. Interleukin-17 (IL-17) and the Type 17 immune signaling pathway cytokine family are recognized for their pivotal role in fostering protective immunity against various pathogens. In this study, we investigate the role of IL-17 and Type 17 immune signaling components during IAPA.MethodsWild-type mice were challenged with influenza A H1N1 (flu) and then exposed to Aspergillus fumigatus ATCC42202 resting conidia on day 6 post-influenza infection, followed by the quantification of cytokines and chemokines at 48 h post-fungal infection.Results and discussionThe gene and protein expression levels revealed that IL-17 and Type 17 immune cytokines and antimicrobial peptides are downregulated during IAPA compared to mice singularly infected solely with A. fumigatus. Restoration of Type 17 immunity was not sufficient to provide protection against the increased fungal burden observed during IAPA. These findings contrast those observed during post-influenza bacterial super-infection, in which restoration of Type 17 immune signaling protects against exacerbation seen during super-infection. Our study highlights the need for future studies to understand the immune mechanisms that increase susceptibility to fungal infection.